Early Detection of Ultra High Risk for Psychosis in a Norwegian Catchment Area: The Two Year Follow-Up of the Prevention of Psychosis Study - Joa, Inge; Bjornestad, Jone; Johannessen, Jan Olav; Langeveld, Johannes; Stain, Helen J.; Weibell, Melissa; Hegelstad, Wenche ten Velden (Frontiers in Psychiatry, 2021)
Objectives: Most individuals experience a relatively long period of sub-clinical psychotic like symptoms, known as the Ultra High Risk (UHR) or At Risk Mental States (ARMS), prior to a first episode of psychosis. Approximately 95% of individuals who will later develop psychosis are not referred to specialised clinical services and assessed during the UHR phase. The study aimed to investigate whether a systematic early detection program, modeled after the successful early detection of psychosis program TIPS, would improve the detection of help-seeking UHR individuals. The secondary aim was to examine the rates and predictors of conversion to psychosis after two years. Method: The overall study design was a prospective (2012-2018), follow- up study of individuals fulfilling UHR inclusion criteria as assessed by the Structural Interview for Prodromal Syndromes (SIPS). Help-seeking UHR individuals were recruited through systematic early detection strategies in a Norwegian catchment area, and treated in the public mental health. Results: In the study period 141 UHR help-seeking individuals were identified. This averages an incidence of 7 per 100,000 people per year. The baseline assessment was completed by 99 of these and the two year psychosis conversion rate was 20%. A linear mixed model regression analysis found that the significant predictors of conversion were the course of positive (0.038) and negative symptoms (0.017). Age was also a significant predictor and showed an interaction with female gender (<0.000). Conclusion: We managed to detect a proportion of UHR individuals in the upper range of the expected prediction by the population statistics and further case enrichment would improve this rate. Negative symptoms were significant predictors. As a risk factor for adverse functional outcomes and social marginalisation, this could offer opportunities for earlier psychosocial intervention.